A physical model on the flame structure of vertical downward turbulent jet fires. (15th February 2023) - Lu, Hongyu; Liu, Shixiang; Lv, Jiang; Li, Xin; Delichatsios, Michael A.; Hu, Longhua
Highlights: Flame morphologic characteristic of vertical downward jet fires quantified. Three regions of a downward jet fire distinguished. A physical model considering momentum, buoyancy and entrainment developed. CFD simulation showing the inner structure of flame conducted. The characteristic length scale for flame geometrical characteristics proposed. Abstract: This work explored the flame geometrical characteristics of vertical downward turbulent jet fires in still air, whose flame buoyancy was opposite to its initial momentum. Experiments were carried out under varied fuel supply rates with propane as fuel. Three circular nozzles having diameters of 3, 5 and 7 mm were employed. CFD simulation to show the combustion structure inside the flame was conducted in the work, contributing to proposing a new physical model. The inner flow field and average mixture fraction of a downward jet fire have been revealed and the CFD result was validated by experimental data. A downward jet fire can be distinguished in three regions: the downward core flow region where the initial flame momentum is opposed by buoyancy, the flow reversal dome region where the momentum reverses direction, and the upward combusting flow region, which surrounds the core, dominated by buoyancy. Three basic flame morphologic lengths of the downward jet fires were measured, namely the flame downward length below the nozzle, the flame width, and the total flame height. The inherent differences between downward, upward and horizontal jet, caused by the momentum direction, were discussed by comparing the flame sizes of these three types of jet flames. A physical model considering the initial downward volumetric momentum, the flame buoyancy and the air entrainment volume until complete combustion occurs was raised to depict the flame geometric characteristics derived from three characteristic length scales, namely a momentum-buoyancy competition length scale, a flow-rate length scale linked with the source diameter and a total combustion buoyancy length scale. All measured experimental flame lengths were normalized using dimensionless groups (such as L m L q and S m ̇ f / ρ ∞ g ′ L m L m 2 ) derived by these three length scales. The geometric properties of downward jet fires were shown to be well modelled by the proposed non-dimensional groups which were different from previously used length scales in the literature.